Aspects Of Time-Dependent Deformation In Hard Rock At Great Depth - K. Drescher (The Southern African Institute of Mining and Metallurgy, 2003)
Excavations in deep level hard rock mines show rheological or time-dependent deformation responses to mining-induced stresses. These are generally not as dramatic as those seen in soft rock environments, such as potash and salt mines, but these deformations can nevertheless become substantial in time. It is usual to see total excavation closure at a much earlier stage than predicted by numerical models, and real-time measurements underground have confirmed that closure takes place on a more-or-less continuous basis, with highest closure rates observed after a blast and then slowly diminishing with passing time. This paper describes laboratory tests to determine the time-dependent response of hard rocks to loading, the results of the tests, and then quantifies these effects to explain the time-dependent phenomena observed underground. The primary intention of this work is to help explain the various time-dependent deformation processes around typical deep level hard rock tabular excavations. Three mechanisms were investigated in two typical hard rock types present in the deep level gold mines in South Africa, namely Ventersdorp Lava and Elsburg Quartzite. Uniaxial compression creep studies were done as the first part of the study followed by shear creep studies on discontinuities where crushed lava and crushed quartzite as well as a natural gouge were used as infilling. The last part of the study consisted of triaxial post-failure relaxation tests. The compression creep tests and the triaxial post-failure relaxation tests showed that the amount of energy dissipated by the lava is significantly less than for quartzite. For mines operating at depths greater than 2000 m the implication is that the lava must show a greater rockburst-proneness than the quartzite. Since the lava shows a lower post-failure stress relaxation, it can store sufficient energy for multiple rockbursts, which is seen in the clustering of multiple seismic events in the deep level mines. This study provides the first data available for energy change calculations in fractured rock masses, and provides the first general indications for rockburst intensities ahead of active mining faces.